The political and the personal: narratives by women with disabilities serving in administrative positions in the Municipal Council - Mangili, Ana Raquel Périco [UNESP]; Pelúcio, Larissa [UNESP] (FapUNIFESP (SciELO), 2024)
In this contribution to feminist disability studies, I seek to analyze the experiences of women with disabilities who occupied/occupy administrative positions in a Municipal Council, highlighting their intersectional experiences. To do so, I used the methodologies of Narrative Research, Content Analysis, Participatory Research, and Intersectional research. As a main result of the study, I obtained confirmation of my initial hypothesis that more than one type of system of oppression is at work when a woman with a disability occupies a public administrative position.
Político e pessoal: as narrativas de mulheres com deficiência na gestão de um conselho municipal
Keywords: Feminist disability studies; Intersectionality; Municipal Council; Narrative research; Women with Disabilities